2021
DOI: 10.1002/cpt.2334
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic‐Guided Therapy in Colorectal Cancer

Abstract: Approximately 20 drugs have been shown to be effective for the treatment of colorectal cancer (CRC). These drugs are from several classes of agents and include cytotoxic drugs, therapeutics that target cell signaling pathways at the extracellular and/or intracellular levels, and combination therapies that contain multiple targeted agents and/or cytotoxic compounds. Targeted therapeutics can include monoclonal antibodies, fusion proteins, and small molecule drugs. The first introduced into clinical use was 5‐fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…2 Molecular profiling of RAS (KRAS, NRAS) and BRAF mutations has revolutionized the treatment of mCRC, as evidenced through guidelines by the National Comprehensive Cancer Network and several other professional societies. [3][4][5][6] Not surprisingly, therefore, recent studies have reported increasing trends in the use of molecular testing in patients with mCRC. 7,8 The presence or absence of certain variations informs the choice of targeted therapies by such agents as epithelial growth factor receptor (EGFR) inhibitors, which are effective in RAS wild-type (WT) left-sided mCRC tumors, and vascular endothelial growth factor (VEGF) inhibitors, used regardless of molecular subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Molecular profiling of RAS (KRAS, NRAS) and BRAF mutations has revolutionized the treatment of mCRC, as evidenced through guidelines by the National Comprehensive Cancer Network and several other professional societies. [3][4][5][6] Not surprisingly, therefore, recent studies have reported increasing trends in the use of molecular testing in patients with mCRC. 7,8 The presence or absence of certain variations informs the choice of targeted therapies by such agents as epithelial growth factor receptor (EGFR) inhibitors, which are effective in RAS wild-type (WT) left-sided mCRC tumors, and vascular endothelial growth factor (VEGF) inhibitors, used regardless of molecular subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular profiling of RAS ( KRAS , NRAS ) and BRAF mutations has revolutionized the treatment of mCRC, as evidenced through guidelines by the National Comprehensive Cancer Network and several other professional societies . Not surprisingly, therefore, recent studies have reported increasing trends in the use of molecular testing in patients with mCRC …”
Section: Introductionmentioning
confidence: 99%
“…From 1950 to 1990, virtually the only drug for the treatment of colorectal cancer was 5-fluorouracil and its derivatives, cytotoxic agents, which are still among the main first-line drugs. Later, other cytotoxic drugs, such as irinotecan (SN-38) and platinum compounds (oxaliplatin), were included in the treatment regimens, and a number of target inhibitors, such as cetuximab, bevacizumab, BRAF inhibitors, and others were discovered somewhat later [ 3 ]. Despite the apparent diversity of drugs and treatment regimens, there are a number of problems associated with these approaches.…”
Section: Introductionmentioning
confidence: 99%
“…5-Fluorouracil (5-FU) is a nonselective chemotherapeutic agent against many types of cancers, including colorectal cancer, , breast cancer, pancreatic cancer, gastric cancer, and head & neck cancer. Especially in the treatment of colorectal cancer, 5-FU is still the first-line chemotherapeutic drug. , However, its short plasma half-life and high incidences of adverse side effects, such as hematological, gastrointestinal, cardiac, neural, and dermatological toxicities, limit wider clinical applications. Evidently, the full anticancer potential of the drug can only be profitably and safely harnessed with much improvement. In the past few decades, two main strategies have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…5-Fluorouracil (5-FU) is a nonselective chemotherapeutic agent against many types of cancers, including colorectal cancer, 1,2 breast cancer, pancreatic cancer, gastric cancer, and head & neck cancer. 3−6 Especially in the treatment of colorectal cancer, 5-FU is still the first-line chemotherapeutic drug.…”
Section: Introductionmentioning
confidence: 99%